The Correlation of Physical Fitness with Dribbling Technique in Football Games - Adil, Ahmad; Ihsan, Andi; Ridwan, Andi (Sains Global Institut, Indonesia, 2023)
This study aims to determine the correlation of physical fitness with the technique of skipping the ball in a football game. This research is quantitative research with a descriptive approach. The method in this study uses descriptive statistics with test and measurement techniques. The population in this study was all students of SD Inpres No. 115 Tabuakang, Jeneponto Regency, aged 10-12 years. The total population is 30 pupils. The sample used in this study was 30 male students of SD Inpres No. 115 Tabuakang, Jeneponto Regency aged 10-12 years with a random sampling technique. The research data used tests and measurements of Indonesia's physical fitness level to determine the level of physical fitness. The results showed that the level of physical fitness was at an average of 14.33 and a standard deviation of 3.044 with a median value of 14.00. While dribbling ability is at an average of 32.1863 and a standard deviation of 4.64335 with a median value of 33.7000. And there is a significant relationship between physical fitness level and dribbling technique.